Incindental Detection of Gall Bladder Carcinoma Post Cholecystectomy Done for Benign Lesions- A Study in a Tertiary Care Centre of North East India - Sarma, Usha; Talukdar, Leena; Bora, Nayana (Asian Pacific Journal of Cancer Biology, 2023)
Background: Incidentally discovered gall bladder cancer (IGBC) is defined as the gall bladder cancer diagnosed during or after the cholecystectomy done for unsuspected benign lesion of GB. There is high incidence of gall bladder carcinoma in North, East, North East and central Indian regions as compared to South and West India. Methods: The present study was conducted at the Gauhati Medical College and hospital (GMCH), Guwahati, Assam for a period of 1 year (January - December 2022). 0.5% cholecystectomy specimens were microscopically diagnosed as incidental gall bladder carcinoma in our study. Results: Most of the cases were well differentiated adenocarcinoma followed by moderately differentiated adenocarcinoma, poorly differentiated, mucinous and papillary adenocarcinoma. Conclusion: Early- stage detection is potentially curative with surgical resection followed by adjuvant therapy. Unresectable or metastatic gall bladder cancers however, qualify for palliative care/ chemotherapy.